Hukum Pengembalian Uang Muka Sewa Sampan Yang Dibatalkan Sepihak Oleh Pemilik Sampan Ditinjau Dari Kompilasi Hukum Ekonomi Syariah (Studi Kasus Desa Teluk Panji, Kecamatan Kampung Rakyat, Kabupaten Labuhanbatu Selatan) - Siti Komariah (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2023)
Legality Of Returning Down Payment For Canoe Rental Unilaterally Canceled By Canoe Owners In Terms Of The Compilation Of Islamic Economic Law (A Case Study in Teluk Panji Village, Kampung Rakyat Sub-district, South Labuhanbatu Regency). In this research, the issues raised are: What are the factors behind the non-refund of down payments for canoe rentals unilaterally canceled by canoe owners in Teluk Panji Village, Kampung Rakyat Sub-district, South Labuhanbatu Regency? What is the opinion of the people in Teluk Panji Village, Kampung Rakyat Sub-district, South Labuhanbatu Regency regarding the unilateral cancellation of down payments for canoe rentals by the canoe owners? What is the legality of returning the down payment for canoe rentals unilaterally canceled by canoe owners in terms of the Compilation of Islamic Economic Law? The aim of this research is to determine the factors, opinions, and the legality of the proper procedure for returning the down payment for canoe rentals. This study is of a juridical-empirical nature, focusing on examining and analyzing the legal behavior of how the law operates in the community. The primary data used in this study was obtained directly from the community through field research methods, employing a case approach. The results of this thesis research reveal a lack of knowledge regarding the proper conduct of leasing and renting in Teluk Panji Village. The practices in this village contradict the provisions of the Compilation of Islamic Economic Law, resulting in the loss of rights and obligations for one party and financial losses in the process of canoe rentals. In the Compilation of Islamic Economic Law, Article 308 states, "The ijarah down payment must be refunded by the mu’ajir if the cancellation of the ijarah is initiated by them." Therefore, the down payment for canoe rentals unilaterally canceled by the canoe owners must be returned.